PENGEMBANGAN BAHAN AJAR FISIKA MENGINTEGRASIKAN NILAI NILAI KARAKTER AL QUR’AN PADA MATERI FLUIDA STATIS DAN FLUIDA DINAMIS UNTUK PEMBELAJARAN SISWA KELAS XI SMA - Fauziah Ulmi (PILLAR OF PHYSICS EDUCATION, 2013)
Government’s effort to develop character education is by integrating it into a lesson. Physics is one of lesson that can develop student’s character. Integrating character value into a lesson needs a teaching material which is integrated by character value. The existing learning material has not entered the character value directly. The aim of this research is to produce a physics learning material which is integrated Al-Quran’s character value that practical, valid, and effective. The object of Research and Development (R&D) are physics learning material which is integrated Al-Quran’s character value and students of XI IPA 2 SMA Negeri 7 Padang. Research instruments are consists of instrument of validity, instrument of practicality, and students learning outcome. Analysis technique of product and data are technique of describing, analysis statistical descriptive, and comparable analysis of correlation. Based on data analysis, the result of research shown that teaching material of Physics which is integrated Al-Quran’s character value are valid, practical, and effective to use in Physics learning.   Keywords: Physics Learning Material, Al-Qur’an’s Character Value, Research and Development